2013
DOI: 10.1097/aud.0b013e31828149f2
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Chronic Tinnitus

Abstract: The authors found gender differences regarding tinnitus-related distress in patients with chronic tinnitus; however, these differences depended on age and in part on duration of tinnitus. Addressing these differences could result in improved, tailored therapy approaches. For instance, applying physical exercise and relaxation techniques could be of special help for older women to reduce their somatic complaints and sleep disturbances. Similarly, cognitive behavioral therapy could reduce their cognitive distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 0 publications
6
41
3
1
Order By: Relevance
“…This finding is similar to the studies carried out separately by Erlandsson et al 9 and Seydel et al 26 in large patient sample sizes, which they reported more females studied but at variance with the report from Salviati et al 12 .…”
Section: Discussioncontrasting
confidence: 47%
“…This finding is similar to the studies carried out separately by Erlandsson et al 9 and Seydel et al 26 in large patient sample sizes, which they reported more females studied but at variance with the report from Salviati et al 12 .…”
Section: Discussioncontrasting
confidence: 47%
“…Even though conflicting data about the role of gender in tinnitus distress exist in literature, it has been shown, irrespective of age, that women were more annoyed by tinnitus and perceived more stress than men did 11 . The slight left ear preponderance of self-reported tinnitus in our study is supported by observation of others that otoneurologic diseases like tinnitus occur more frequently in the left ear than in the right 12 …”
Section: Discussionmentioning
confidence: 99%
“…Modern therapy concepts recommend a tailored approach in planning the therapy (Seydel et al, 2013). Similarly, for an inpatient-setting, evaluated therapy concepts are available by now (Täuber, 2012).…”
Section: Resultsmentioning
confidence: 99%